2005
DOI: 10.1172/jci23183
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of integrin β6 during the epithelial-mesenchymal transition defines a novel prognostic indicator of aggressive colon carcinoma

Abstract: We used a spheroid model of colon carcinoma to analyze integrin dynamics as a function of the epithelialmesenchymal transition (EMT), a process that provides a paradigm for understanding how carcinoma cells acquire a more aggressive phenotype. This EMT involves transcriptional activation of the β6 integrin subunit and a consequent induction of αvβ6 expression. This integrin enhances the tumorigenic properties of colon carcinoma, including activation of autocrine TGF-β and migration on interstitial fibronectin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
191
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 192 publications
(211 citation statements)
references
References 33 publications
17
191
2
1
Order By: Relevance
“…An interesting observation from this work was the additive effect of Ets-1 and αvβ6 expression on each other, wherein patients who were positive for both Ets-1 and αvβ6 expression relapsed earlier than patients who are positive for Ets-1 or αvβ6 alone [37]. These findings were supported by previous work by Bates et al who also demonstrated the transcriptional activation of β6 by Ets-1 correlated with poor patient survival [30]. Peng et al investigated the interplay between Ets-1 and αvβ6 expression on the 5-year survival rates of 158 patients from Qilu Hospital (Shandong University, China), though it is important to note that patients with elevated risk factors were encouraged to take adjuvant chemotherapy, of which 87 (55.1 %) received 5-fluorouracil (5-FU)-based adjuvant chemotherapy [37].…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations
“…An interesting observation from this work was the additive effect of Ets-1 and αvβ6 expression on each other, wherein patients who were positive for both Ets-1 and αvβ6 expression relapsed earlier than patients who are positive for Ets-1 or αvβ6 alone [37]. These findings were supported by previous work by Bates et al who also demonstrated the transcriptional activation of β6 by Ets-1 correlated with poor patient survival [30]. Peng et al investigated the interplay between Ets-1 and αvβ6 expression on the 5-year survival rates of 158 patients from Qilu Hospital (Shandong University, China), though it is important to note that patients with elevated risk factors were encouraged to take adjuvant chemotherapy, of which 87 (55.1 %) received 5-fluorouracil (5-FU)-based adjuvant chemotherapy [37].…”
Section: Introductionsupporting
confidence: 86%
“…In terms of patient survival, the phenotypic transition from a lymph node negative Duke's stage B tumour to a nodal positive metastasis (Duke's stage C) is a crucial step in disease progression [40], and so this would be one likely transition where one might expect to observe upregulation of poor prognostic indicators [37,30]. As this was not the case in either study, it is possible that other pro-metastatic factors (e.g.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…There is now overwhelming evidence for its role in the clinical progression of multiple human epithelial malignancies (colon, ovary, and brain), both from the in situ to the invasive stage as well as from the invasive stage to regional and distant metastasis 5, 6, 7. The addition of breast cancers to this long list of epithelial cancers where integrin α v β 6 plays a role in clinical progression is more recent.…”
Section: Introductionmentioning
confidence: 99%